(untitled) (Research, Society and Development, 2021)
Antibiotic residues can be widespread in the environment due to the lack of adequate water and wastewater treatment systems. The aim of this study was to conduct a literature review on the occurrence of antibiotics in aquatic matrices and to describe the national and international legal and regulatory devices. This is a narrative review. Articles published from 2008 to 2018 were selected. The study showed that countries have sought to expand the monitoring of some emerging contaminants that were not previously the subject of legal devices. Europe is more advanced in monitoring, while in the United States the regulation is only for drinking water. In Brazil, there is still no legal provision for any type of drug and the sewage treatment systems are not adequate for the removal of these water pollutants, which may pose a threat to aquatic environments and antimicrobial resistance that is a global public health emergency.